We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
159
1
avatar+4116 

Help 14

 Mar 19, 2018
 #1
avatar+100439 
+2

14

First term  =  6(1) - 4  =  2

16th term  =  6(16) - 4  =  92

Sum  = 

(first term + last term) (number of terms) / 2  =

 (2 + 92) * 16/2  =   94 * 8   = 752   

 

 

15.  Similar to 14

First term  = 4(1) - 3  = 1

!0th term  = 4(10) - 3  =  37

Sum  =

(1 + 37) * 10/ 2  =

38 * 5  =

190

 

 

cool cool cool

 Mar 19, 2018

9 Online Users